System approach to grazing in desert ecosystems: a case study in Saudi Arabia - Mirreh M.M. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
This paper highlights a system approach to grazing in a desert ecosystem used by the Range and Animal Development Research in the northern region of the Kingdom of Saudi Arabia. Various factors affecting plant and animal production in a high potential desert system (wadi bottom) are discussed. The use of cultural treatments for increased forage production, the effect of protection and flock management for reduced grazing pressure are among the different aspects studied for the integrated management of rangeland resources, which have considerable implication in combating desertification. A summary of major results from the various research topics is reported.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)